REKONSTRUKSI PERLINDUNGAN KONSUMEN DALAM TRANSAKSI PERBANKAN SYARIAH DI ERA DIGITALISASI FINANSIAL - Cemara, Rina Biyan Ramadani Eddy; Nagga, Jumaedi (IAIN Parepare, 2025)
The digital transformation of the financial services sector, particularly within Sharia banking, has brought about significant changes that reshape transaction patterns, the relationship between consumers and financial institutions, and the legal frameworks that support them. While digitalization promotes efficiency, financial inclusion, and accessibility, it also introduces new vulnerabilities technical, contractual, and related to compliance with Sharia principles that may adversely affect consumers. This conceptual article is based on a literature review of 30 national and international scholarly articles published in the last five years, focusing on consumer protection, digital financial services, and Sharia legal ethical principles. Employing a normative-juridical approach and conceptual analysis, the study explores the intersection of consumer protection regulations, the values of maqāṣid al-sharī‘ah, and emerging legal challenges within the digital financial landscape. The findings indicate a critical need to reconstruct the paradigm of consumer protection in digital Sharia banking. This reconstruction must transcend formal legal approaches by integrating principles of contractual justice, digital transparency, institutional accountability, and adaptive Sharia ethics. Consequently, consumer protection must be designed not only to respond to digital risks but also to prevent them while remaining consistent with the foundational tenets of Islamic law.